The Drosophila melanogaster flightless-I gene involved in gastrulation and muscle degeneration encodes gelsolin-like and leucine-rich repeat domains and is conserved in Caenorhabditis elegans and humans. - Campbell, H.D.; Schimansky, T.; Claudianos, C.; Ozsarac, N.; Kasprzak, A.; Cotsell, J.; Young, I.G.; de Couet, H.G.; Miklos, G.L.G. (Proceedings of the National Academy of Sciences of the United States of America, 1993)
Mutations at the flightless-I locus (fliI) of Drosophila melanogaster cause flightlessness or, when severe, incomplete cellularization during early embryogenesis, with subsequent abnormalities in mesoderm invagination and in gastrulation. After chromosome walking, deficiency mapping, and transgenic analysis, we have isolated and characterized flightless-I cDNAs, enabling prediction of the complete amino acid sequence of the 1256-residue protein. Data base searches revealed a homologous gene in Caenorhabditis elegans, and we have isolated and characterized corresponding cDNAs. By using the polymerase chain reaction with nested sets of degenerate oligonucleotide primers based on conserved regions of the C. elegans and D. melanogaster proteins, we have cloned a homologous human cDNA. The predicted C. elegans and human proteins are, respectively, 49% and 58% identical to the D. melanogaster protein. The predicted proteins have significant sequence similarity to the actin-binding protein gelsolin and related proteins and, in addition, have an N-terminal domain consisting of a repetitive amphipathic leucine-rich motif. This repeat is found in D. melanogaster, Saccharomyces cerevisiae, and mammalian proteins known to be involved in cell adhesion and in binding to other proteins. The structure of the maternally expressed flightless-I protein suggests that it may play a key role in embryonic cellularization by interacting with both the cytoskeleton and other cellular components. The presence of a highly conserved homologue in nematodes, flies, and humans is indicative of a fundamental role for this protein in many metazoans.